Flapping wings in line formation flight: a computational analysis. (May 2014) - Ghommem, M.; Calo, V. M.
Abstract: The current understanding of the aerodynamics of birds in formation flights is mostly based on field observations. The interpretation of these observations is usually made using simplified aerodynamic models. Here, we investigate the aerodynamic aspects of formation flights. We use a potential flow solver based on the unsteady vortex lattice method (UVLM) to simulate the flow over flapping wings flying in grouping arrangements and in proximity of each other. UVLM has the capability to capture unsteady effects associated with the wake. We demonstrate the importance of properly capturing these effects to assess aerodynamic performance of flapping wings in formation flight. Simulations show that flying in line formation at adequate spacing enables significant increase in the lift and thrust and reduces power consumption. This is mainly due to the interaction between the trailing birds and the previously-shed wake vorticity from the leading bird. Moreover, enlarging the group of birds flying in formation further improves the aerodynamic performance for each bird in the flock. Therefore, birds get significant benefit of such organised patterns to minimise power consumption while traveling over long distances without stop and feeding. This justifies formation flight as being beneficial for bird evolution without regard to potential social benefits, such as, visual and communication factors for group protection and predator evasion.